ZnO(N)-Spiro-MeOTAD hybrid photodiode: an efficient self-powered fast-response UV (visible) photosensor - Game, Onkar; Singh, Upendra; Kumari, Tanya; Banpurkar, Arun; Ogale, Satishchandra (Nanoscale, 2014)
Organic-inorganic hybrid photo-detectors with a self-sufficient mode of operation represent a research area of great current interest. In most efficient photodetectors and optoelectronic devices compound semiconductors containing toxic elements such as Cd, As, Te, S, Se etc. are used and these are also expensive. Hence there is also a rapidly growing interest in replacing these with environmentally friendly and earth-abundant materials. Herein, we report a facile solution-processed fabrication of a self-powered organic-inorganic hybrid photodetector using n-type oriented ZnO nanorods and p-type Spiro-MeOTAD semiconductor. ZnO is eco-friendly and earth-abundant, and Spiro-MeOTAD is nonhazardous. We show that the latter has far less toxicity than the toxic elements stated above. This visible blind UV photodetector shows high sensitivity (10(2)) and a UV/visible rejection ratio of 300. It also exhibits fast response times of tau(rise) similar to 200 mu s and tau(fall) similar to 950 mu s. Importantly, with a small modification of nitrogen incorporation in ZnO one can also realize a highly-sensitive self-powered visible light photodetector with at least 1000% (or higher) improvements in quality factors (photocurrent/sensitivity/response time) as compared to previously reported organic-inorganic hybrid photo-detectors based on metal-chalcogenides (CdS-PANI or CuInSe2-P3HT). Interestingly, the broadband sensitivity of such N:ZnO-Spiro-MeOTAD photodiode enables sensing of low intensity (similar to 28 mu W cm(-2)) ambient white light with a high photocurrent density of 120 nA cm(-2) making it an efficient ambient white light detector.